北極圏の氷河上クリオコナイトのストロンチウム同位体比の地理分布 - 本田彩奈; 竹内, 望; 永塚, 尚子; 中野, 孝教; Ayana, Honda; Nozomu, Takeuchi; Naoko, Nagatsuka; Takanori, Nakano (2013)
Sr stable isotopic ratios (87Sr/86Sr) in cryoconite on glaciers in Arctic region were analyzed to identify sources of constituents of the cryoconite. The cryoconite samples that we analyzed were collected from glaciers in Canada (Sveldrup, Greenshield and Coronation Glaciers) and Svalbard (Foxfonna and Longyearbreen Glaciers). The results were also compared with the values of Greenland and Alaska, which were measured in previous studies. The isotopic ratio significantly varied among glaciers. The isotopic ratio of silicate mineral fraction was highest (above 0.74) in the cryoconite of Penny ice cap of Canada, while middium in those in Devon, Svalbard, and Greenland glaciers, and lower in those of an Alaskan glacier. This variation suggest that sources of mineral particles of cryoconite are not unique in those Arctic glaciers, but are different among geographical locations. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） conference object